Analisis Hadis Riwayat Al-Tirmidzi Tentang Pendidikan Akal Menggunakan Aplikasi Jawami’ Al-Kalim - Deden Hilmansah; Aulya Fazrin Rahman (al-Afkar, Journal For Islamic Studies, 2022)
Analysis Of History Of Al-Tirmidzi About Reasoning Education Using Jawami' Al-Kalim Application  Intellectual education is a very important thing, even ijtihad as the fruit of reason thinking is one of the most important sources of law in Islam. This study aims to analyze: 1) understanding of reason education 2) comparison of the hadith of al-Tirmidhi's history of reason education 3) the process of transmission and quality of the hadith of al-Tirmidhi's history of reason education 4) istimbath and application of the content of the hadith of al-Tirmidhi's history about intellectual education on the theory or practice of Islamic education. The research approach used is qualitative research with library research instruments and the research method used is descriptive method. In analyzing this hadith the author uses the help of the Jawami 'al-kalim application. The results of this study provide the following conclusions: 1) mind education is to shape the mindset of students towards everything that is useful, whether in the form of syar'i science, culture, modern science, awareness, thought, and civilization; 2) this hadith was narrated by several narrators such as Muhammad bin Isha At-Tirmidhi in the book Jami'u At-Tirmidhi hadith number 1245, Ahmad bin Hanbal in the Musnad Ahmad bin Hanbal book hadith number 21492, Abu Daud in the book Sunan Abi Daud hadith number 3121 and Abdullah bin Abul Ar-Rahman Ad-Darimy in the book of Sunan Darimi hadith number 168; 3) this hadith is a dho'if hadith but is a maqbul min hadith hasan li ghairi; 4) the results of the istimbath hadith show that the Prophet Muhammad provided broad opportunities for the development of reason in order to bring together humans with their own nature. This is relevant to the concept of education, namely reason and intellect must be developed.